2018
DOI: 10.1007/s10854-018-9351-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of InGaN/GaN/Al2O3 structure from reciprocal space mapping

Abstract: By using metal organic chemical vapor deposition technique, InGaN/GaN solar cell (SC) structure is deposited over sapphire (Al 2 O 3) wafer as GaN buffer and GaN epitaxial layers. Structural properties of InGaN/GaN/Al 2 O 3 SC structure is investigated by using high resolution X-ray diffraction technique dependent on In content. By using reciprocal space mapping, reciprocal space data are converted to w-θ data with a software. These w-θ data and full width at half maximum data are used for calculating lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This shift of the N 1s core level state to higher binding energy is attributed to N dangling bonds [58,59]. 102) planes of GaN, respectively [34,[60][61][62]. A small peak at 40.20 • corresponds to β-Ga 2 O 3 (402) and is consistent with the XPS analysis [63].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This shift of the N 1s core level state to higher binding energy is attributed to N dangling bonds [58,59]. 102) planes of GaN, respectively [34,[60][61][62]. A small peak at 40.20 • corresponds to β-Ga 2 O 3 (402) and is consistent with the XPS analysis [63].…”
Section: Resultssupporting
confidence: 74%
“…High-resolution XRD of the GaN TF is shown in Figure 4. Diffraction peaks are observed at 34.58 • and 48.25 • and correspond to the (002) and (102) planes of GaN, respectively[34,[60][61][62]. A small peak at 40.20 • corresponds to β-Ga 2 O 3 (402) and is consistent with the XPS analysis[63].…”
supporting
confidence: 73%
“…It was observed that the ω − 2θ and omega XRC diffraction pattern of asymmetric peak (1 0 −1 5) of InGaN layer lost its sharpness in the intensity and its symmetry deteriorated after implantation resulted in mixed asymmetric GaN and InGaN peaks. This type of tricking diffraction patterns can be resolved using RSM [12]. Additionally, mosaic defects with high accuracy can be investigated.…”
Section: Resultsmentioning
confidence: 99%